2022
DOI: 10.1002/ppap.202100247
|View full text |Cite
|
Sign up to set email alerts
|

A poly‐diagnostic study of the shield gas‐assisted atmospheric pressure plasma jet propagation upon a dielectric surface

Abstract: The significance of shield gases on atmospheric pressure plasma jet (APPJ) propagation over a horizontal dielectric surface using various diagnostic methods has been investigated. The obtained results imply that adding nitrogen as a shield gas only has an impact on the N 2 reactive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Finally, comparing the argon mass fraction of the second and third row of figure 10(b) implies that when all three channels are supplied with argon gas, a highly homogeneous gas mixture is attained, as argon atoms diffuse effectively. Prior studies have reported that plasma jets tend to propagate towards a higher concentration of the same gas [54]. Thus, when all three channels are filled with argon, the argon from the middle and outer channels reacts substantially in the semiclosed volume inside the cap, effectively mingling with the plasma-generating argon channel, significantly expanding the size of the plasma effluent.…”
Section: Cfd Simulationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, comparing the argon mass fraction of the second and third row of figure 10(b) implies that when all three channels are supplied with argon gas, a highly homogeneous gas mixture is attained, as argon atoms diffuse effectively. Prior studies have reported that plasma jets tend to propagate towards a higher concentration of the same gas [54]. Thus, when all three channels are filled with argon, the argon from the middle and outer channels reacts substantially in the semiclosed volume inside the cap, effectively mingling with the plasma-generating argon channel, significantly expanding the size of the plasma effluent.…”
Section: Cfd Simulationsmentioning
confidence: 96%
“…In addition to characterizing the plasma temperature, 2D numerical simulations of fluid dynamics are carried out to gain a fundamental understanding on how different gas channels mix and how gas propagates in ambient air. This method has been used before to visualize gas behavior patterns that can subsequently be correlated with plasma propagation [23,54]. The size of the gas channel can be linked to the plasma dimensions, so the mole fraction of argon can indicate where the ignited plasma might spread in the real plasma jet system [55].…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…However, this method restricts the flexibility of the APPJ application. A more promising approach involves using a coaxial quartz tube to create an annular space for the APPJ, where a selected gas composition is supplied to shield the ambient air [16,17,[21][22][23][24]. Shielding gas can also control the plasma chemistry to produce ROS or RNS.…”
Section: Introductionmentioning
confidence: 99%